The impact of the ICTY on the former Yugoslavia: an anticipatory postmortem - Milanović, Marko (American Society of International Law, 2016)
As a series of public opinion surveys indicate, the International Criminal Tribunal for the Former Yugoslavia seems not to have persuaded populations in the various successor countries that the findings in its judgments are true. These surveys highlight strong relationships between the respondents' ethnicity, their perception of the ICTY's bias against their group, and their distrust of the ICTY and of its findings.